Bacterial and Microeukaryotic Community Compositions and Their Assembly Processes in Lakes on the Eastern Qinghai-Tibet Plateau - Dandan Wang; Yuefei Huang; Haichao Jia; Haijiao Yang (Microorganisms, 2023)
Bacterial and microeukaryotic community compositions and their assembly processes have remained challenging and remained unclear in lake ecosystems on the Qinghai-Tibet Plateau (QTP). We revealed the diversity and community compositions, driving factors, ecological assembly processes, and co-occurrence networks of bacterial and microeukaryotic communities in water bodies of the eight lake ecosystems across the Eastern QTP. The results demonstrated that the predominant bacteria in most samples were Proteobacteria, with an average relative abundance of 41.78%, whereas the most abundant of microeukaryotes differed among the sample sites. The redundancy analysis revealed that latitude and pH were the most important driving factors in shaping the bacterial and microeukaryotic community compositions. Homogeneous selection (56.40%) was the dominant process in assembling the bacterial communities, whereas dispersal limitation (67.24%) was the major process in governing the microeukaryotic communities. Furthermore, dissolved organic carbon and salinity were the major factors mediating the balance of deterministic and stochastic assembly processes in the bacterial and microeukaryotic communities. Both the bacterial and microeukaryotic community co-occurrence networks exhibited topological features of modularity and non-random topological features. The results offer insights into the mechanisms underpinning bacterial and microeukaryotic diversities and communities in the lake ecosystems on the QTP.